The peculiarities of the current stage of development of the Armenian community in the UAE - Mangassarian-Menkechian, Chake (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Արաբական Միացեալ Էմիրութիւններում (ԱՄԷ) հայկական համայնքի զարգացումը XXI դարու սկիզբը նշանագրուած է մի քանի յատկանշական առանձնայատկութիւններով, որոնք հետեւանք էին մի կողմից ԱՄԷ-ի պետական կեանքի զարգացման, միւս կողմից՝ ներհայկական իրադարձութիւններուն: Ուսումնասիրութեան հիմնական թեմա դարձած են ազգային մշակոյթի պահպանման քաղաքականութիւնը, հայկական մամուլը, համայնքային իրադարձութիւնները, ներգաղթն ու արտագաղթը, ինչպէս նաեւ հայապահպանումի աշխատանքներն ու համապատասխան կառոյցներու՝ եկեղեցիներու, միօրեայ եւ կիրակնօրեայ վարժարաններուն ստեղծումը: Армянская общинa в Объединенных Арабских Эмиратах в начале XXI века характеризуется рядом примечательных особенностей, являющихся результатом прогрессивного социально-экономического развития ОАЭ, что сказывается на внутриобщинной жизни. Ключевую роль в сохранении национальной идентичности играет армяноязычная периодика как основа поддержания национальной культуры и как рупор проблем, волнующих членов Диаспоры. Важной составляющей жизни Диаспоры являются воскресные школы, способствующие формированию национального самосознания посредством обучения на армянском языке и приобщения к армянской истории и культуре. The evolution of the Armenian community in the United Arab Emirates (UAE) in the early 21st century is characterized by distinct features influenced by both the state’s development and internal Armenian dynamics. This article delves into the key aspects of the community’s progress in the UAE, focusing on cultural preservation, Armenian media, community activities, migration patterns, and efforts to uphold Armenian heritage through institutions like churches and one-day and Sunday schools. With a history spanning nearly five decades – though the formal establishment of the Armenian community in the UAE is commonly recognized as dating to 1980 – the community has successfully adapted to shifting global and local contexts, particularly in the realm of technology and its impact on Armenian identity. These shifts have significantly shaped community life, often foreshadowing specific developments.
Keywords: History